The problem of literary value - Meyer-Lee, Robert J. (Manchester University Press, 2023)
Literary value – in the sense of the worth, usefulness or importance of the literary – has been a topic of debate from no later than Plato’s impugning of poetry. But from the so-called canon wars of the last century to the present, literary value has also become a perplexing source of distress. With its complicities thoroughly unmasked, it no longer axiomatically serves as literary study’s central justification. Yet no consensus alternative has taken its place. This book, unlike other approaches to the topic, neither pursues an apologetic thesis about the most defining values of literature nor conversely provides a demystifying account of the ideological uses of specific ascribed values. Instead, arguing that the category of literary value is ultimately inescapable, it focuses pragmatically on everyday scholarly and pedagogical activities, proposing how we may reconcile that category’s inevitability with our understandable wariness of its intractable uncertainties and complicities. Toward these ends, it offers a preliminary theory of literary valuing and explores the problem of literary value and possible responses in respect to the literary edition, canonicity and interpretation. Much of this exploration occurs within Chaucer studies, which, because of Chaucer’s simultaneous canonicity and marginality, provides fertile ground for thinking through the problem’s challenges. The book thereby also supplies an extended reflection on the state of Chaucer studies. In using this subfield as a kind of synecdoche for the field as a whole, the book seeks to forge a viable rationale for literary studies within and without the academy.